IMPLEMENTASI RCCM (RIVEST CIPHER 4 BASED ON CHAOTIC MAPPING) PADA PESAN TEKS MENGGUNAKAN GUI PYTHON - Adidtya Perdana; Nurul Ain Farhana (LPPM Universitas Deli Sumatera, 2023)
In securing a message, especially digital messages, a technique or algorithm is needed in the field of cryptography. Where cryptography itself is a scientific field in informatics and computer science that discusses and learns about securing a secret message. One of the algorithms or in cryptography is called a Cipher, which can be used to secure secret messages, namely RCCM. RCCM or Rivest Cipher 4 base on Chaotic Mapping is a development of RC4 which combines it with the Chaotic Map technique. RC4 itself is a cryptographic algorithm that belongs to the Stream Cipher. In the process of securing messages on RC4, key generation is carried out using KSA (Key Scheduling Algorithms) and PRGA (Pseudo-Random Generation Algorithm) which are processed based on the key entered by the user to produce a keystream. The keystream itself consists of a series of random numbers, each of which will be exclusive or (XOR) to the plaintext that produces the ciphertext. By applying the Chaotic Map, inputting the key by the user is not necessary. And for implementation, you can use Python programming and are GUI-based using the help of the Tkinter library.